2022
DOI: 10.1002/advs.202105307
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional π‐Conjugated Additives for Halide Perovskite

Abstract: Additive is a conventional way to enhance halide perovskite active layer performance in multiaspects. Among them, π‐conjugated molecules have significantly special influence on halide perovskite due to the superior electrical conductivity, rigidity property, and good planarity of π‐electrons. In particular, π‐conjugated additives usually have stronger interaction with halide perovskites. Therefore, they help with higher charge mobility and longer device lifetime compared with alkyl‐based molecules. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 165 publications
(335 reference statements)
2
40
0
Order By: Relevance
“…[34] Unlike the conventional VBM and CBM of most 2D perovskite materials located on the inorganic layer, the π-electrons in 1-NA, BIDZ, and DPDA molecules have a significant contribution to CBM, which can lead to a reduced bandgap of layered perovskites, and promote the absorption of photons by the perovskite to generate more electron-hole pairs and facilitate charge transport. Meanwhile, we speculate that the 𝜋 and 𝜋* states located in the near-edge CB can also facilitate the electronic coupling between the organic layers and the inorganic layers, optimizing the mobility of carriers and more favorable photovoltaic performance, which is consistent with that reported by Xiao et al [35] This is also proved by the DOS result under other dimensions (n = 2, 3) (Figure S3a-d, Supporting Information).…”
Section: Resultssupporting
confidence: 90%
“…[34] Unlike the conventional VBM and CBM of most 2D perovskite materials located on the inorganic layer, the π-electrons in 1-NA, BIDZ, and DPDA molecules have a significant contribution to CBM, which can lead to a reduced bandgap of layered perovskites, and promote the absorption of photons by the perovskite to generate more electron-hole pairs and facilitate charge transport. Meanwhile, we speculate that the 𝜋 and 𝜋* states located in the near-edge CB can also facilitate the electronic coupling between the organic layers and the inorganic layers, optimizing the mobility of carriers and more favorable photovoltaic performance, which is consistent with that reported by Xiao et al [35] This is also proved by the DOS result under other dimensions (n = 2, 3) (Figure S3a-d, Supporting Information).…”
Section: Resultssupporting
confidence: 90%
“…A boosted stability observed from the PSCs based on the PEA 2 PbI 4 :MAPbI 3 thin film reveals that the 2D perovskites indeed play a very important role in preventing perovskites from moisture and air. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Moreover, superior stability observed from the PSCs based on the Nd 3+ -substituted PEA 2 PbI 4 :MAPbI 3 thin film indicates that the substitution of Pb 2+ by heterovalent Nd 3+ could restrict the ion migration and suppress defects within the resultant perovskites, resulting in boosted stability of perovskites.…”
Section: Device Performance Of Pscsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] To circumvent this problem, conjugated organic molecules as the organic spacers were used to create 2D perovskites. [29][30][31][32][33][34] For example, we demonstrated high-performance PPVs based on the 2D:3D mixed perovskites, where 2D perovskites were based on conjugated organic molecules, 3-phenyl-2-propen-1-amine and 4-fluorobenzylammonium. [32][33][34] On the other hand, previous studies indicated that the utilization of metal cations to partially substitute Pb 2+ can boost the charge transport of 3D perovskites.…”
mentioning
confidence: 99%
“…[4] existence of intermolecular π-π interaction. [28] It could be speculated that the functional group would improve the ability to transfer carriers through the perovskite interfaces and GBs.…”
Section: Introductionmentioning
confidence: 99%